Digital processing of images of extruded rubber profiles for process control MRI. (March 2016) - Perlo, Josefina; Mülder, Christoph; Danieli, Ernesto; Hopmann, Christian; Blümich, Bernhard; Casanova, Federico
Graphical abstract: Highlights: A new algorithm to delineate the shape of extruded rubber profiles from images. Magnetic resonance imaging gives contactless access to inner and outer surfaces. The digital accuracy meets industrial tolerances. Abstract: Magnetic resonance imaging (MRI) is a powerful technique in materials science, in particular for the analysis of polymer and rubber materials. So far the use of this technique for quality control has not been fully explored mainly because of the prohibitive costs and maintenance associated with conventional MRI tomography systems. This constraint has been removed recently since robust and mobile desktop tomographs with permanent magnets have become available at reduced cost. In this work we apply an image processing chain algorithm to MR images of rubber profiles recorded with a desktop MRI scanner. Although the nominal spatial resolution of MR images is inherently lower than that of optical methods, we demonstrate that the digital resolution achieved after the image processing steps allows one to determine the spatial positions of the inner and outer contours with 50 μm precision. Using this information it is then possible to measure structural dimensions of the rubber profiles, such as wall thickness or internal voids, with precisions that are of the same order of magnitude as those observed with CT or camera imaging.